Experimental research collaborates in the Scientific Methodology teaching-learning process: an experience in Agronomic Engineering (Research, Society and Development, 2022)
Scientific methodology is a component present in the pedagogical project of several degree courses. However, students are generally uninterested over this subject. Curricular component has been approached in many cases in an expository and fragmented way not allowing students to understand and apply the content approached which compromises success in student learning. Thus, the aim was to present the experience with students of the bachelor’s degree in Agronomic Engineering at the Instituto Federal do Amapá - Campus Porto Grande, Amapá, Brasil, through an experimental research as a form of collaboration in the teaching-learning process. Initially, there was a theoretical approach to the contents along with the students and then the experiments were conducted. After that, the students tabulated data, performed statistical analysis and the report writing with teacher monitoring. After all the steps for conducting a scientific research – including agricultural experimentation in the field and discussion of the importance of each research step – the work resulted in the presentation of a final research report according to the standardization of the Brazilian Association of Technical Standards. Students who were involved in the pedagogical experience have been interested in the component and usage of experimental research contributes to the teaching-learning process. Experimental research in the area of student training has made the activity close to the students reality and proved effective in addressing the content of scientific methodology.